IMPLEMENTATION AND CHALLENGES OF ONLINE LEARNING MODELS IN THE PANDEMIC ERA IN ELEMENTARY SCHOOLS IN ACEH BESAR DISTRICTS - Andrian, Restu; Rassanjani, Saddam; Syukran, Syukran (Idaarah: Jurnal Manajemen Pendidikan, 2023)
The Covid-19 pandemic forces the education sector to implement distance learning (online). For schools and people who are familiar with Information Technology (IT), online learning is not a problem. However, this condition will be different for schools and people who are unfamiliar with IT, especially for community groups who are living in the outside of urban and rural areas. This study wants to see how online learning is applied in elementary schools. This research uses a qualitative approach, data or information obtained from the process of observation and interviews with people who are undergoing online learning in Aceh Province. There are many obstacles to home learning for low-income economies and people living in rural areas. For this community group, doing online learning is challenging, starting from the problem of facilities, parental support, to children’s motivation in this kind of learning. The implementation of online learning in rural and low-class economic communities does not meet expectations, it can even be said to be unsuccessful. This condition is caused by limited access and inadequate learning media.